Gendering struggles against informal and precarious work - Agarwala, Rina, 1973-; Chun, Jennifer Jihye, 1973- (Political power and social theory, 2019)
This volume examines how gender shapes the varying and intersecting dynamics of informal/precarious worker struggles in two gender-typed sectors - domestic work and construction. Drawing upon cases across the global North and South, it explores how gender is intertwined into collective organizing efforts, why gender is addressed and to what end.